El pluralismo jurídico y el estado constitucional de derechos de la República del Ecuador - Guerrero Portillo, Diana Esperanza (2022)
The present investigation called legal pluralism and the Constitutional State of Rights of the Republic of Ecuador, had as a general objective\; determine the effectiveness of legal pluralism in the constitutional State of law and justice of the Republic of Ecuador, through a qualitative approach, through a descriptive level, a normative method and the application of the documentary technique and the interview, having as a result The main thing is that in order to guarantee legal pluralism, human rights, due process, the social unity of the State and the national and international norms that regulate indigenous justice, adequate coordination and cooperation between ordinary and customary justice is required, but also of a special law that allows covering all those guidelines, limits, prohibitions, guarantees, jurisprudence that encompasses the protection of the collective rights of indigenous peoples and nationalities, without failing to ignore the diversity of ancestral and customary norms, which are part of its own right, managing to conclude that legal plurality requires of normative parameters based on an adequate protection of human rights by the indigenous authorities, in order to determine its effectiveness in the Constitutional State of Rights, plurinational, intercultural and the jurisprudence of the Constitutional Court, at a linguistic, legal, economic level , political and social, by reason of article 171 of the Magna Carta.